Conservation and biodiversity preservation activities a comparative insight between conservation regions in Cross River State, Nigeria and Berbak and Sembilang National Parks, Indonesia - Muhammad Rianzar; Raldi Hendro Koestoer (Bioculture Journal, 2026)
Background: Biodiversity conservation in protected areas is a global concern, requiring collaborative efforts across nations to safeguard Earth's ecological integrity. This study examines conservation and biodiversity preservation activities in the Cross River State Protected Areas, Nigeria, and the Berbak and Sembilang National Parks, Indonesia. Methods: Through an in-depth literature review, the research analyses the biodiversity conditions, threats, conservation approaches, legal frameworks, constraints, and strengths in both areas. Findings: Findings reveal significant biodiversity richness coupled with serious threats from unsustainable human activities, including deforestation, illegal hunting, and mining. Conservation initiatives involve governments, non-governmental organizations, and local communities, encompassing conservation education, alternative livelihood support, and law enforcement. However, constraints such as limited resources, inter-agency coordination, and community conflicts hinder conservation effectiveness. To enhance biodiversity preservation, a comprehensive and collaborative approach is proposed, emphasizing capacity building for local communities, strict law enforcement, incentive provision, and regional cooperation. Conclusion: An examination of the conservation and biodiversity preservation initiatives undertaken within the safeguarded regions of Cross River State in Nigeria and the Berbak and Sembilang National Parks in Indonesia reveals a tapestry of contrasting approaches and shared commonalities. Despite being endowed with exceptional biodiversity richness, both countries face severe threats to its sustainability, such as deforestation, illegal hunting, and unsustainable human activities. Novelty/Originality of this article: Ultimately, this research contributes to understanding the challenges and opportunities in biodiversity conservation, serving as a foundation for developing sustainable policies and strategies in Nigeria, Indonesia, and other countries with similar characteristics.